The Impact of Technology on Education (PAI) and Social Dynamics - Hayatul Khairi (BiCED Proceeding, 2024)
The impact of technology on education also affects the social dynamics of society. With increasing access to information, society becomes more educated and aware of social issues, including the values of Pancasila and national identity. However, on the other hand, the entry of alternative ideologies through the internet can pose challenges to traditional values held by society. This study uses a qualitative research method. Data sources are divided into two, namely primary data sources and secondary data sources with data collection techniques through observation, interviews and documentation. Technology offers many benefits in Islamic Religious Education education, it is important to be aware of and overcome the negative impacts that may arise so that the learning process remains effective and in accordance with the religious values held. Technology provides many positive benefits in Islamic Religious Education, from increasing accessibility and interactivity to supporting lifelong learning. However, it is important to use technology wisely so that these positive impacts can be maximized. Technology has many positive impacts on students' social dynamics, from increasing interaction and access to information to developing social skills and social awareness. By using technology wisely, students can enrich their learning experiences and build better relationships with others. Its negative impact on students' social dynamics needs to be considered. It is important to create a balance between technology use and healthy social interactions so that students can develop optimally both academically and socially..